Climbing bean as a solution to increase productivity in land-constrained environments: Evidence from Rwanda - Katungi, Enid M.; Larochelle, Catherine; Mugabo, Josephat R.; Buruchara, Robin Arani (SAGE Publications, 2019)
Climbing bean is a potential solution to increase the agricultural sector productivity and sustainability. Using nationally representative bean-producing household data collected in Rwanda, this study identifies factors that influence the decision to switch from cultivating bush to climbing bean and quantifies the impact of climbing bean adoption on yield. About 50% of bean-producing households grow climbing bean, a substantial increase over the past 15 years. Elevation, population pressure, and drought shocks are important drivers of climbing bean adoption. Adoption of climbing bean increases yield by 23% among adopters and has the potential to increase yield by 48% for non-adopters. Findings from this study provide important information for the development of agricultural policies and programs in Rwanda and elsewhere.